PUBLIC SERVICE INNOVATION ANALYSIS THE TEN-MINUTE ENTRY INFORMATION SYSTEM OF THE CITY IS COMPLETED (SIP MAS HAR) AT THE DEPARTMENT OF INVESTMENT AND INTEGRATED ONE DOOR SERVICE OF PATI REGENCY - Inka Putri Nur Indras Wari; Ari Subowo; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Innovation in public services is essential to tackling the problems available to boost quality public service. SIP MAS HAR is one of the innovation in public services at city admission in DPMPTSP of Pati Regency to obtain faster, easier, and transparent licensing services. The study was done to analyze the innovation SIP MAS HAR whether it had gone well or not using the attribute theory of innovation in accordance with Rogers and the factors that impedes innovation. Qualitative descriptive methods are used by collecting data from observation, 2 interview and documentation. Research shows that SIP MAS HAR innovation was doing well, considering the attribute theory of innovation had a relative advantage, compatibility, triability, and observability, but it was still complexity. In addition, there are inhibitors to SIP MAS HAR innovation that depend more on high performers, no awards or incentives, limited infrastructure, budgets and lack of human resources in the permissive field. The recommendation of researchers is widespread direct socialization of communities in order to understand online registration and can tap into technology, In addition to pt gamatechno, there is an expert outsourching of non-commissioned employees, the need for special budget allocation for innovation improvements and development, giving credit or incentives to those who implement innovation to be motivated and fired on the job.